(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Manual garden tools help a lot with different types of work with soil: digging, removing roots and weeds, harvesting root crops and bulbs, and much more would be much more difficult if it were not for the forks. This tool has a wide range of features. There are many varieties of this tool differing in shapes and sizes: manure, harvesting, hay, flower, pointed, fork-shovel, telescopic, digging, ball-pointed. A common problem for all manual garden forks is clogging of the tines. This reduces the productivity of those who use them. Attempts are constantly being made to solve the problem of quick cleaning of the tines of manual garden forks. Many technical solutions to this problem are patented and are actively used in practice. The employee of the FSBEI of Higher Education “Pskov State University” has developed a manual self-cleaning fork. The design of the manual self-cleaning fork consists of a handle and a frame with many elongated spaced tines, which is fixed at one end of the handle, as well as a cleaning plate that is fixed to the movable handle, and a spring located on top of the handle inside the movable handle. The movable handle has lateral longitudinal grooves. The movable handle provides movement of the cleaning plate relative to the handle, and, consequently, compression and releasing of the spring. The overall dimensions of the proposed device are accepted according to the existing standards for such structures. The principle of operation of the proposed device: during the operation of the fork, the cleaning plate is pressed against the frame by spring force. Cleaning of the tines is made by a cleaning plate, which is moved along the tines. To do this, the user withdraws the movable handle, overcoming the resistance of the spring. By doing so, the frame passes through the longitudinal grooves and serves as one guide for the movable handle, and the handle serves as the second guide. The fork returns to its original state by releasing the spring after the user releases the movable handle. The main technical result of the proposed device is an increase in the operational characteristics of the fork, reduction in the time and effort spent on cleaning of the tines.